Actualité et inactualité de la stagification - Emmanuel Triby (Éducation et Socialisation)
This article offers a critical analysis of the text which initiated this review and of the notion of “stagification” then suggested by its author in 1975. The dated and orientated nature of this first document allows a reinterpretation of current developments in adult training. This article examines the theoretical implications that the idea of “stagification“ could entail nowadays. This rereading opens up to the possibility of an original interpretation of the “work placement” proliferation phenomenon in initial training, especially in higher education.